Sanitation and Environmental Health in the surroundings of areas with social habitation in Salvador — BA (Research, Society and Development, 2020)
The analysis of indicators related to environmental health in social conglomerates can provide subsidies for decision making to public managers. In this focus, we sought to associate the configurations of environmental health (sanitary infrastructure) and risk of occurrence of leptospirosis cases, in the vicinity of the 31 areas with buildings of the Minha Casa Minha Vida Program, lane 1, in Salvador - BA. The methodological strategy adopted incorporated the use of geoprocessing techniques, for the spatialization of health infrastructure configurations, with the creation of thematic and density maps. Considering the hotspots generated, it was observed that the process of selecting areas for the implementation of social housing projects obeys an exclusive logic, concentrating vulnerable socioeconomically people in environmentally fragile places, implying a greater susceptibility to the occurrence of neglected diseases. A preventive public investment in basic sanitation is considered as a strategic assumption, as a state and / or municipal counterpart, due to the logic of curative health economics. Still, it should be a pre-requisite of planning, the parameters of environmental health to the entrepreneurs in the selection process, approval / release of development, execution of works and "get used" to the users of social housing in these tangential urban areas.